Potensi Tanaman Sebagai Pencerah Wajah Alami - Rina Mustika; Siti Hindun; Nurul Auliasari (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Melanin is a pigment that gives human skin, hair and eye color. Excessive distribution of pigment malanin can cause skin problems such as hyperpigmentation. One of the principles of handling hyperpigmentation is to inhibit melanin synthesis which can be done by using a depigmentation agent (tyrosinase inhibitor) which has a mechanism of action to inhibit the tyrosinase enzyme. Inhibition of the tyrosinase enzyme can be done by measuring IC50 in a plant. IC50 is the concentration of an inhibitor needed to inhibit half of the enzyme activity. This review aims to compare the IC50 values ??of monophenolase activity and IC50 diphenolase activity in some plants that have tyrosinase inhibitory activity with invitro testing methods on L-tyrosine or L-DOPA substrates. The results of the study of several articles found that the plants that have the best potential to reward tyrosinase enzyme activity are sweet root extract (Glycyrrhiza glabra L.) with IC50 value 126.7548 µg / mL on the activity of diphenolase and extract of bark (Nauclea subdita) with IC50 value of 568.58 µg / mL on monofenolase activity.